' Loperamide overdose induces ventricular tachycardia with catastrophic outcomes' - Zain Ali; Umer Shoukat; Mariya Khan; Sohaib Roomi; Waqas Ullah (Greater Baltimore Medical Center, 2020)
Loperamide is a widely available, over-the-counter medication. The advent of the opioid epidemic has seen cases of loperamide overdose being reported. The common side effects of the medication can be relatively benign, but at high doses, loperamide can precipitate life-threatening arrhythmias. Our case highlights rare side effects of loperamide overdose inducing ventricular tachycardia, with unfavorable consequences. This case emphasizes that the distribution and availability of this medication should be restricted, to be a prescription drug, to prevent overdose and adverse outcomes.